2022
DOI: 10.15446/agron.colomb.v40n2.102900
|View full text |Cite
|
Sign up to set email alerts
|

Use of reduced Bokashi doses is similar to NPK fertilization in iceberg lettuce production

Abstract: The aim of the study was to compare horticultural variables of iceberg lettuce using two Bokashi compost doses, alone and in combination, with the bioactivator Penergetic (Penergetic International AG®) against standard mineral fertilization (NPK) in three crop cycles. Experiments were conducted in a plastic greenhouse at the Universidade Estadual de Londrina, Brazil (548 m a.s.l.). The treatments were: negative control (water, only); positive control (NPK, 4-14-8); Penergetic alone; Bokashi doses 5 g and 10 g/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 19 publications
0
0
0
Order By: Relevance
“…In similar studies, Souza et al (2017) concluded that using Penergetic brings positive results and benefits in soybean production, increasing the grain yield by adding only NPK + micronutrients. Lima et al (2022) suggest the incorporation of additional organic matter to evaluate the effects of Penergetic throughout cultivations, and Franco et al (2018) point out that effective bioactivators require an adequate level of organic matter. In the present study, the organic matter content is considered medium (20 g dm -3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In similar studies, Souza et al (2017) concluded that using Penergetic brings positive results and benefits in soybean production, increasing the grain yield by adding only NPK + micronutrients. Lima et al (2022) suggest the incorporation of additional organic matter to evaluate the effects of Penergetic throughout cultivations, and Franco et al (2018) point out that effective bioactivators require an adequate level of organic matter. In the present study, the organic matter content is considered medium (20 g dm -3 ).…”
Section: Resultsmentioning
confidence: 99%
“…A commercially accessible solution of natural soil microbes with beneficial properties is Efficient Microorganisms (EM), also known as Bokashi, which means fermented organic material composed of aerobic and anaerobic microbes. Yet another source reported as a soil and plant bioactivator is Penergetic, which, according to the manufacturer, increases the photosynthetic efficiency of plants (Penergetic-P) and improves the performance of organic matter in decomposing soil organisms (Penergetic-K) (Hata et al 2021, Lima et al 2022).…”
mentioning
confidence: 99%